Achieving tunability of effective electromagnetic wave absorption between the whole X-band and Ku-band via adjusting PPy loading in SiC nanowires/graphene hybrid foam. (June 2018) - Cheng, Yehong; Hu, Ping; Zhou, Shanbao; Yan, Liwen; Sun, Boqian; Zhang, Xinghong; Han, Wenbo
Abstract: To synthesize lightweight and high-performance electromagnetic wave absorbing composite, SiC nanowire (SiCnw) and conductive polymer polypyrrole (PPy) were incorporated in graphene aerogel (GA) via chemical vapor infiltration combined with a simple chemical polymerization method. The SiCnw/GA with filler loading of 20 wt% has an effective absorption bandwidth of 5.1 GHz in the frequency range of 8.0–13.1 GHz covering the whole X band. After coating on PPy film, the SiCnw/GA-43 wt% PPy sample has an effective absorption bandwidth of 5.9 GHz in frequency range of 12.1–18.0 GHz covering the whole Ku-band at a very thin thickness of 1.83 mm. When adjusting the PPy loading to 66 wt%, the effective absorption bandwidth of SiCnw/GA-PPy could reach a high value of 6.4 GHz in frequency of 8.2–14.6 GHz covering the whole X-band at a thin thickness of 2.32 mm. Therefore, the SiCnw/GA-PPy foams could achieve tunability of effective absorption between the whole X-band and Ku-band by adjusting the loading of PPy or SiCnws. In SiCnw/GA-PPy absorbing materials, interfacial polarization, relaxation polarization loss, electronic dipole polarization and electrons hopping are major determining factors of superior electromagnetic wave absorption properties. The SiCnw/GA-PPy foams with excellent comprehensive performance are promising candidates as electromagnetic wave absorbing materials. Graphical abstract: Image 1